Impact of the novel MRI contrast agent gadopiclenol on radiotherapy decision making in patients with brain metastases - Sarria, Gustavo R.; Fleckenstein, Jens; Eckl, Miriam; Stieler, Florian; Ruder, Arne Mathias; Bendszus, Martin; Schmeel, Christopher; Koch, David; Feißt, Andreas; Essig, Marco; Wenz, Frederik; Giordano, Frank Anton (Investigative radiology, 2025)
Purpose - The aim of this study was to assess the effect of gadopiclenol versus gadobenate dimeglumine contrast-enhanced magnetic resonance imaging (MRI) on decision-making between whole-brain radiotherapy (WBRT) and stereotactic radiosurgery (SRS) for treatment of brain metastases (BMs). - Methods - Patients with BMs underwent 2 separate MRI examinations in a double-blind crossover phase IIb comparative study between the MRI contrast agents gadopiclenol and gadobenate dimeglumine, both administered at 0.1 mmol/kg. The imaging data of a single site using identical MRI scanners and protocols were included in this post hoc analysis. Patients with 1 or more BMs in any of both MRIs were subjected to target volume delineation for treatment planning. Two radiation oncologists contoured all visible lesions and decided upon SRS or WBRT, according to the number of metastases. For each patient, SRS or WBRT treatment plans were calculated for both MRIs, considering the gross target volume (GTV) as the contrast-enhancing aspects of the tumor. Mean GTVs and volume of healthy brain exposed to 12 Gy (V12), as well as Dice similarity coefficient scores, were obtained. The Spearman rank (ρ) correlation was additionally calculated for assessing linear differences. Three different expert radiation oncologists blindly rated the contrast enhancement for contouring purposes. - Results - Thirteen adult patients were included. Gadopiclenol depicted additional BM as compared with gadobenate dimeglumine in 7 patients (54%). Of a total of 63 identified metastatic lesions in both MRI sets, 3 subgroups could be defined: A, 48 (24 pairs) detected equal GTVs visible in both modalities; B, 13 GTVs only visible in the gadopiclenol set (mean ± SD, 0.16 ± 0.37 cm3); and C, 2 GTVs only visible in the gadobenate dimeglumine set (mean ± SD, 0.01 ± 0.01). Treatment indication was changed for 2 (15%) patients, 1 from no treatment to SRS and for 1 from SRS to WBRT. The mean GTVs and brain V12 were comparable between both agents (P = 0.694, P = 0.974). The mean Dice similarity coefficient was 0.70 ± 0.14 (ρ = 0.82). According to the readers, target volume definition was improved in 63.9% of cases (23 of 36 evaluations) with gadopiclenol and 22.2% with gadobenate dimeglumine (8 of 36), whereas equivalence was obtained in 13.9% (5 of 36). - Conclusions - Gadopiclenol-enhanced MRI improved BM detection and characterization, with a direct impact on radiotherapy treatment decision between WBRT and SRS. Additionally, a more exact target delineation and planning could be performed with gadopiclenol. A prospective evaluation in a larger cohort of patients is required to confirm these findings.